Efficacy and safety of the S1PR modulator etrasimod in the treatment of moderately to severely active ulcerative colitis during the induction phase: a systematic review and meta-analysis of randomized controlled trials - Qiu, Jingyue; Liu, Jiakuo; Cai, Kexin; Xu, Ting; Liu, Wenwen; Lin, Fei; Shi, Ning (Frontiers in Pharmacology, 2024)
The study aims to assess the efficacy and safety of the recently approved S1PR modulator etrasimod in adults with ulcerative colitis (UC) during the induction phase through meta-analysis.Methods: A systemic search was performed for randomized controlled trials evaluating the efficacy and safety of the S1PR modulator etrasimod using electronic databases PubMed, Embase, the Cochrane Library, Clinical Trials, and the International Clinical Trials Registry Platform. Three studies with 943 patients met the inclusion criteria and were included in this analysis. The study's primary endpoint was the proportion of patients who achieved clinical remission at week 12. Key secondary endpoints included the proportion of patients with clinical response, endoscopic improvement, and histologic remission. The incidence of AEs, serious AEs, and AE-related treatment discontinuation were statistically analyzed to determine the safety of etrasimod.Results: This study revealed that etrasimod is superior to placebo at the primary endpoint clinical remission (OR = 3.09, 95% CI: 2.04 -4.69), as well as at the secondary endpoints clinical response (OR = 2.56, 95% CI: 1.91 -3.43), endoscopic improvement (OR = 2.15, 95% CI: 1.51 -3.05), and histologic remission (OR = 3.39, 95% CI: 2.03 -5.68). The proportion of patients with TEAE (OR = 1.34, 95% CI: 1.01 -1.78) and SAE (OR = 0.77, 95% CI: 0.41 -1.43) was similar between the etrasimod and placebo groups. Patients receiving etrasimod had slightly higher odds of experiencing headache (OR = 2.07, 95% CI: 1.01 -4.23), and nausea (OR = 1.84, 95% CI: 0.72 -4.72). The incidences of upper respiratory tract infection (OR = 0.79, 95% CI: 0.27 -2.32), nasopharyngitis (OR = 0.40, 95% CI: 0.15 -1.07), and urinary tract infection (OR = 1.82, 95% CI: 0.59 -5.60) were generally lower in the etrasimod groups and no treatment-related serious infections were reported.This study demonstrates that etrasimod is effective in treating moderately to severely active UC with a favorable benefit-risk profile at week 12. Etrasimod shows promise as a potential first-line oral therapy for individuals suffering from this disease. Additional RCTs with larger sample sizes and longer observation periods are needed to confirm the sustained efficacy of etrasimod beyond the initial phase